Ten Years After the 2008 Crisis: Has Risk Aversion Won? - Eliana Marcia Martins Fittipaldi Torga; Carolina Magda da Silva Roma; Paula Magda Roma; Bruno Pérez Ferreira (BBR: Brazilian Business Review)
The aim of this paper is to investigate the performance of low-volatility portfolio strategies representing risk aversion after the 2008 global financial crisis. Five investment portfolios were built by taking into consideration the weight distribution criteria defined by the inverse of the standard deviation of assets, the natural logarithm and exponential of these values, as well as the minimum variance and tangent portfolios, based on the S&P 500 futures index, dollar futures index, US government long-term bond (10-year Treasury Bond) and gold futures. The design of the strategies used both twelve- and thirty-month rolling windows for the standard deviation and conditional volatility estimates. Mean return of portfolio, risk through standard deviation, Sharpe index, and risk-adjusted return were calculated for evaluation purposes. Results have evidenced that, together, risk-based portfolios using 12-month rolling window or conditional volatility were superior to the tangent portfolio, as well as that the minimum variance portfolio was competitive to other alternatives. The main contribution of the current study lies in the fact that risk aversion was relevant to portfolios’ performance in the post-crisis period.